Мішана задача для двовиміpної гіпеpболічної системи пеpшого поpядку - Кміть, І.Я. (Видавничий дім "Академперіодика" НАН України, 2008)
Using an analog of the classical method of characteristics for one-dimensional hyperbolic systems, we investigate a mixed problem for a two-dimensional semilinear hyperbolic system with non-Lipschitz nonlinearities. We prove that the problem is correctly posed in the classical sense.